METHODIC PARTICULARITIES REGARDING THE STUDENTS’ TRAINING IN THE BASIC TECHNIQUE OF ALPINE SKIING (GYMNASIUM, 2009)
Elaborating theoretical papers, where there dominates the idea of researching and experimentationregarding the tendencies and perspectives of skiing in general, and of alpine skiing in particular, representsone of the major preocupations of the specialists in the domain who, through their activity, push forward thetheory and methodics in skiing training, finding the most efficient methods and techniques of initiation andlearning.The main goal of the paper in the activity of learning the skiing technique is that of forming into thesubjects, through the indirect way, the system of motive abilities and skills that couls allow them a safe andefficient crossing of the areas covered by snow.The topic of the present paper and implicitly of the performed activities for its study emphasized thefact that some elements, not enough elaborated, can be factors that limit the progress of the instructedsubjects.